A Bayesian analysis of boar spermatozoa kinematics and head morphometrics and their relationship with litter size fertility variables. Issue 7 (18th May 2021) - Barquero, Vinicio; Soler, Carles; Sevilla, Francisco; Calderón‐Calderón, Josué; Valverde, Anthony
Abstract: The semen movement and sperm head size patterns of boar ejaculates were analysed using computer‐assisted semen analysis (CASA)‐Mot and ‐Morph systems. The aim of the present study was to compare morphometric and kinematics variables from boars and to determine the relationship with sow fertility variables related to litter size. The females were from maternal crossing schemes such as the continuous 3‐generation cross between York (Y), Landrace (L), and Pietrain (P) hybrid sows and Pietrain boars. Semen samples were collected from 11 sexually mature boars from two sire lines. Samples were analysed using the ISAS ® v1 system to evaluate eight kinematic variables of sperm velocity, progressiveness and undulations. Four morphometric parameters of sperm head size (length, width, area and perimeter) were analysed. Bayesian analysis revealed relevant differences in four kinematic variables (VSL, LIN, STR and WOB) between sire lines, with a probability of relevance ( P R ) of 0.79–0.91, and Pietrain boars were associated with higher progressive motility compared with Duroc x Pietrain boars. Moreover, there were relevant differences in all morphometric variables ( P R = 0.82–0.85) between sire lines. The dam line Y‐L‐50 (½ Y × ½ L) had higher total born per litter and piglets born alive, and YLP‐75 ( 1 /8 Y × 1 /8 L × 3 /4 P) was associated with higher values of litter weight at birth (highest posterior density region at 95% = 9.92, 16.41 kg). There are relevant differences in kinematic variables between the assessed sire lines and the differences in morphometric and litter size variables were also relevant. The York‐Landrace hybrid sows had higher total born per litter and piglets born alive, and there were relevant differences when compared with YLP‐50 (¼ York × ¼ Landrace × ½ Pietrain). Differences in kinematic and morphometric variables between sire and dam lines related to fertility need to be further studied.